Hubungan Crisis Mental Health Emergency dan Psychological First Aid dengan Kesiapan Psikologis Masyarakat Menghadapi New Normal Infeksi Coronavirus 2019 - Diah Priyantini; Nursalam Nursalam; Tintin Sukartini (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
The COVID-19 pandemic continues to increase and has transformed into a troubling case for many people to cause mass paranoia, it is necessary to be psychologically prepared to face the new normal era. The purpose of this study was to analyze the relationship between crisis mental health emergency and psychological first aid with the psychological readiness of the community. The design of this study was a quantitative study with a cross sectional approach. A sample of 521 respondents was taken using a convenience sampling technique which was carried out by the study in July 2020. The independent variables of the study were mental health emergency and psychological first aid, while the dependent variable was the psychological readiness of the community. The instruments used were a crisis mental health emergency questionnaire, psychological first aid and Social Psychological Survey of COVID-19. The data were analyzed using the SPSS version 22.0 statistic tested by Spearman rho. The results of the study showed that mental health emergency crisis and psychological first aid had a significant relationship with psychological readiness. Based on the test results, the p value for crisis mental health emergency was 0.017 and psychological first aid was 0.012, both p values were less than 0.05, so the H0 hypothesis was rejected. The strength of the correlation in the mental health emergency crisis showed a result of 0.61, which was a strong relationship, while the psychological first aid variable showed a result of 0.83, which was a very strong relationship. The psychological readiness of the community is closely related to the mental health crisis and the psychological readiness of the community in facing COVID-19. Keywords: coronavirus disease 2019; psychological first aid; mental health crisis ABSTRAK Pandemi COVID-19 terus mengalami peningkatan dan telah menjelma menjadi kasus yang membuat resah bagi banyak orang hingga menimbulkan paranoid massal, perlu untuk dilakukan kesiapan psikologis dalam menghadapi era normal baru. Tujuan dari studi ini adalah untuk menganalisis hubungan crisis mental health emergency dan psychological first aid dengan kesiapan psikologis masyarakat. Desain dari penelitian ini adalah penelitian kuantitatif dengan pendekatan cross sectional. Sampel sebanyak 521 responden diambil menggunakan tekhnik convenience sampling yang dilaksanakan penelitian pada Bulan Juli 2020. Variabel independent penelitian adalah crisis mental health emergency dan psychological first aid, sedangkan variabel dependen adalah kesiapan psikologis masyarakat. Instrumen yang digunakan adalah crisis mental health emergency questionnaire, psychological first aid dan Social Psychological Survey of COVID-19. Data kemudian dianalisis menggunakan statistic SPSS versi 22.0 yang diuji dengan Spearman rho. Hasil penelitiana menunjukkan bahwa crisis mental health emergency dan psychological first aid memiliki hubungan yang signifikan dengan kesiapan psikologis. Berdasarkan hasil pengujian, didapatkan nilai p untuk crisis mental health emergency adalah 0,017 dan psychological first aid adalah 0,012, kedua nilai p kurang dari 0,05 sehingga hipotesis H0 ditolak. Kekuatan korelasi pada crisis mental health emergency menunjukkan hasil 0,61 yaitu hubungan yang kuat, sedangkan pada variabel psychological first aid menunjukkan hasil 0,83 yaitu memiliki hubungan yang sangat kuat. Kesiapan psikologis masyarakat sangat erat hubungannya dengan kondisi krisis Kesehatan mental dan kesiapan psikologis masyarakat dalam menghadapi COVID-19. Kata kunci: coronavirus disease 2019; psychological first aid; mental health crisis